Chemical constituents and phytochemical properties of floral maize pollen - Bujang, Japar Sidik (Public Library of Science, 2021)
Currently, bee-gathered pollen (bee pollen) is commonly used worldwide as a dietary supplement and is recognized for its curative properties. Floral pollen is also important but is less recognized due to a lack of investigation. This study aims to determine the morphological characteristics and nutritional and phytochemical properties of floral maize pollen. Fresh pollen grains harvested from a farm of maize plants are yellow in colour and spheroid in shape. They change to amber and indented prismatic solid shapes when dehydrated. The main composition of floral maize pollen is carbohydrates (44.30±3.73%), followed by moisture (23.38±5.73%), crude proteins (17.16±3.13%), crude fibres (9.56±0.92%), and ash (4.98±0.11%), while the lowest content is observed for crude fats (0.62±0.06%). The predominant mineral is potassium (768.50±11.40 mg 100 g-1), followed by sodium (695.10±9.70 mg 100 g-1), calcium (147.20±12.60 mg 100 g-1), and magnesium (97.30±2.9 mg 100 g-1). The microelements (with average values) consist of iron (49.50±3.30 mg 100 g-1) and zinc (30.00±3.70 mg 100 g-1). Excellent phytochemical properties add value to floral maize pollen. Maize pollen contains a high total phenolic content (TPC) and total flavonoid content (TFC) of 783.02 mg GAE 100 g-1 and 1706.83 mg QE 100 g-1, respectively, and possesses strong antioxidant activity of 10.54 mg mL-1. Maize floral pollen and derived products can serve as future food resources for human consumption and as a source of functional and bioactive compounds in nutraceutical and pharmaceutical industries.